Agency Theory, Accounting Information, and Corporate Financial Management: A New Framework for Developing Financial Strategies for Banking Companies - Choirunnisa Arifa (The Indonesian Journal of Accounting Research, 2017)
Abstract: The objective of this study is to develop a corporate financial optimization model, based on the theoretical foundations of, and for integrating, the crucial issues in accounting and finance such as agency and information asymmetry and the use of accounting information to mitigate the problems, which can give appropriate financial strategies relevant for the contemporary business world. There are a good number of financial models in the existing literature. However, as important issues relevant to financial management for corporations are emerging, it is essential to develop a financial optimization model that can embed and address these emerging issues and can prescribe a set of financial management strategies, which are relevant in the current situations of corporations shaped by these emerging issues. This study formulates an applied integrated financial optimization problem to investigate the extent to which the financial model designs optimal financial strategies that can mitigate agency problems and provide a basis for sound accounting practices, leading to the optimal company value in real life situations. Generally, this study concludes that the integrated financial model can provide economic significance when formulating financial strategies for mitigating agency problems and maximizing company value. It also provides new insights into sound accounting practices should be implemented in an integrated, large-scale real-life financial strategy. This paper contributes to corporate financial modeling by developing a model based on the multidisciplinary literature, including contemporary accounting, agency theory, and management science, by providing a new corporate finance model, which is appropriate for modeling and addressing some crucial contemporary issues in corporate finance in the current world.Abstrak: Tujuan dari penelitian ini adalah untuk mengembangkan model optimasi keuangan perusahaan, berdasarkan pada landasan teoritis, dan untuk mengintegrasikan isu-isu penting dalam akuntansi dan keuangan seperti asimetri agensi dan informasi dan penggunaan informasi akuntansi untuk mengurangi masalah, yang dapat memberikan strategi keuangan yang tepat yang relevan untuk dunia bisnis kontemporer. Ada sejumlah model keuangandalamliteratur yang sudahada. Namun, karena isu-isu penting yang relevan dengan manajemen keuangan untuk perusahaan sedang berkembang, penting untuk mengembangkan model pengoptimalan keuangan yang dapat menanamkan dan mengatasi masalah yang muncul dan dapat meresepkan serangkaian strategi manajemen keuangan, yang relevan dalam situasi perusahaan saat ini. dibentuk oleh isu-isu yang muncul ini. Studi ini merumuskan masalah optimasi keuangan terintegrasi yang diterapkan untuk menyelidiki sejauh mana model keuangan merancang strategi keuangan yang optimal yang dapat mengurangi masalah keagenan dan menyediakan dasar untuk praktik akuntansi yang baik, yang mengarah ke nilai perusahaan yang optimal dalam situasi kehidupan nyata. Umumnya, penelitian ini menyimpulkan bahwa model keuangan terintegrasi dapat memberikan signifikansi ekonomi ketika merumuskan strategi keuangan untuk mengurangi masalah keagenan dan memaksimalkan nilai perusahaan. Ini juga memberikan wawasan baru ke dalam praktik-praktik akuntansi yang baik harus diterapkan dalam strategi finansial kehidupan nyata berskala besar yang terintegrasi. Makalah ini memberikan kontribusi untuk pemodelan keuangan perusahaan dengan mengembangkan model berdasarkan literatur multidisiplin, termasuk akuntansi kontemporer, teori keagenan dan ilmu manajemen, dengan menyediakan model keuangan perusahaan baru, yang sesuai untuk pemodelan dan mengatasi beberapa isu kontemporer yang krusial dalam keuangan perusahaan. di dunia saat ini.